Sistem Pengelompokan Jenis Sampah Rumah Tangga untuk Optimalisasi Pengolahan - Ishlakhuddin, Fauzan; Muhamad, Fachrul Pralienka Bani; Ismantohadi, Eka (Politeknik Harapan Bersama, 2025)
The increasing volume of household waste in Indonesia has raised the need for efficient waste management solutions. This study developed an Internet of Things (IoT)-based waste classification system aimed at optimizing waste processing. The system integrates digital scales, ESP32 microcontrollers, and cloud-based servers to collect, monitor, and manage waste data in real-time. Using the Prototype Software Development Life Cycle (SDLC) method, the system was designed, implemented, and evaluated iteratively to meet user needs effectively. The system allows users to input waste type, verifies the data with a PIN, and transmits it to a server for centralized management. Testing results demonstrated high accuracy in weight measurements, consistency between devices, and seamless data integration into the system. The IoT-based system not only reduces operational workload but also supports efficient recycling by categorizing waste with economic value. Further research is recommended to expand the system's application to larger communities and explore its integration into broader waste management platforms.